Weight losses caused by Prostephanus truncatus (Horn.) (Coleoptera: Bostrichidae) and Araecerus fasciculatus Degeer (Coleoptera: Anthribidae) to dried yam chips - Danjuma, S.; Ayertey, J.N.; Codjoe, A.R. (Journal of Medical and Pharmaceutical Sciences, 2008)
The weight loss caused by P. truncatus and A. fasciculatus to dried yam chips following artificial infestation with the above-named insects was studied in the laboratory under ambient temperature and relative humidity conditions. Three varieties of yams – “Asaana”, “Pona” (Discorea rotundata Poir) and “Afasie” (D. alata L.) were used. The yam chips were produced following four treatments– Parboiled Oven dried (PO), Non- parboiled Oven dried (NO), Parboiled Sun dried (PS), and Non- parboiled Sun dried (NS) chips. The PS and NS yam chips showed significantly more weight losses than PO and NO yam chips after infestation by the two experimental insects. P. truncatus caused less weight loss to PO and NO yam chips. A. fasciculatus was unable to breed and survive on these treatments. Mixed populations of both insects studied caused significantly less weight losses to dried yam chips compared to the single species insect population. Based on variety differences, “Afasie” dried yam chips showed more significant weight loss than that suffered by “Asaana” and “Pona”. No significant difference was however observed in the weight losses between “Asaana” and “Pona” varieties. The highest numbers of adult emergence were recorded on the parboiled sun dried and non-parboiledl sun dried yam chips for all varieties of yam used for both P. truncatus and A. fasciculatus.
Keywords: Yam Chips; Asana; Pona; Afasie; P. truncatus; A. fasciculatus